Morfometri parasitoid nyamuk ganjur alang-alang asal Kabupaten Cianjur, Jawa Barat - Kiki Fajrina Simamora; Nina Maryana; Purnama Hidayat (Jurnal Entomologi Indonesia, 2022)
Imperata cylindrica is a species of grass that causes economic losses. One of the insects reported to have the potential as a biological control agent for Imperata is the cogongrass gall midges, Orseolia javanica (Diptera: Cecidomyiiae). The development of the cogongrass gall midges is influenced by its natural enemies, not much is known about the parasitoids of this cogongrass gall midges. This study aims to identify and describe the morphological and morphometric characters of the cogongrass gall midges parasitoids. This research was conducted from July 2018 to June 2019. The gall cogongrass was collected from bunds rice fields in Cianjur District, West Java. Rearing the gall cogongrass and morphometric measurements was conducted at the Insect Biosystematics Laboratory, Plant Protection Department, Faculty of Agriculture, IPB University. Three species of parasitoids were found in cogongrass gall midges, i.e. Platygaster orseoliae (Hymenoptera: Platygasteridae), Aprostocetus sp. (Hymenoptera: Eulophidae), and Propicroscytus mirificus (Hymenoptera: Pteromalidae). The results of morphometric measurements of the parasitoids cogongrass gall midge showed that the female body length of P. orseoliae is 0.65–0.98 mm, and the male body length is 0.69–1.07 mm. The body length of the female Aprostocetus sp. is 1.51–2.02 mm and male body length is 1.13–1.29 mm. Female body length of P. mirificus is 4.14–4.46 mm. Principal component analysis showed that the parasitoid P. orseoliae had no difference between males and females, Aprotocetus sp. females have a larger body size than males, and P. mirificus has the largest body size compared to other parasitoids.